2013
DOI: 10.1089/jpm.2012.0610
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Barriers to Pain Management in Patients Receiving Outpatient Palliative Care

Abstract: Background: Patient-reported barriers are an important obstacle to cancer pain management. For effective pain management, exploring patient-reported barriers and related factors is important. Objectives: The study's objective is to determine factors associated with patient-reported barriers to cancer pain management. Method: We conducted a secondary analysis of data from a prospective observational study examining opioid adherence in palliative care outpatients. We evaluated the association between high score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…Indeed, nonwhite patients tended to have communication problems, which might have led to their receiving less aggressive care. These findings are similar to the results of our previous study of cancer pain management, in which nonwhite patients showed higher pain management barriers than white patients (p=0.02) [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, nonwhite patients tended to have communication problems, which might have led to their receiving less aggressive care. These findings are similar to the results of our previous study of cancer pain management, in which nonwhite patients showed higher pain management barriers than white patients (p=0.02) [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…20 Barriers to pain relief are reported more commonly for nonwhite patients. 21,22 Studies also suggest that people who are socioeconomically disadvantaged may not be fully believed when they are reporting pain, and they may receive less than adequate pain control. 23,24 The underlying causes of these disparities include interactions between the patient and the clinician along with environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al [17] state that pain is a common symptom that diminishes the quality of life of the patients, however, it still is not sufficiently addressed. Eyigor [18] in his study observes that 34.3% of surveyed medical students believe that the use of opioids was insufficient in cancer patients, whereas 54.3% of them stated that pain management was ting the competent persons who would be able to provide assistance at any time.…”
Section: Discussionmentioning
confidence: 99%